Methylglyoxal-Induced Retinal Angiogenesis in Zebrafish Embryo: A Potential Animal Model of Neovascular Retinopathy - Ying Li; Yantao Zhao; Shengmin Sang; TinChung Leung (Journal of Ophthalmology)
Methylglyoxal (MG) is an intermediate of glucose metabolism and the precursor of advanced glycation end products (AGEs) found in high levels in blood or tissue of diabetic patients. MG and AGEs are thought to play a major role in the pathogenesis of diabetic retinopathy. In order to determine if zebrafish is valuable to help us understand more about retinopathy, we evaluate if MG induces abnormal vascular change and angiogenesis in zebrafish in a short incubation period. We also used an inhibitor of VEGFR (PTK787) to explore the mechanistic role of VEGF in MG-induced pathogenesis. A transgenic Tg(flk1:GFP) zebrafish line was used, and the embryos were incubated with MG solution and in combination with glucose (to mimic hyperglycemia). Retinal vascular structure visible with fluorescence signal was imaged using fluorescence microscopy. The percentage of vascular area was calculated and found elevated in the MG treatment groups than that in the control group (p<0.01) which indicated increased angiogenesis induced by MG treatment. PTK787 blocked the proangiogenic effects of MG treatment. This study suggests that MG has a potential proangiogenic effect via VEGF signaling in the retina of zebrafish embryos. Therefore, this zebrafish model may be used to study neovascular retinopathy.